Evaluasi Kebijakan Fiskal dan Moneter Indonesia Selama Krisis (Studi Kasus: Pandemic Covid-19) - Misnanto; Susanto (Jurnal EMT KITA, 2025)
The Covid-19 pandemic requires a country to strive for health care and also maintain economic stability from potential crises. The purpose of this study is to evaluate various types of policy implementations that synergize between state institutions, to strive for safety and maintain a robust economy. Evaluation of the implementation of these policies can be measured based on the Implementation as A Political and Administrative Process model. The results of the study convey that the government intervenes in fiscal and monetary matters, fiscal stimulus is intended to increase the budget allocation for handling the Covid-19 pandemic, while monetarily the government focuses on lowering interest rates and increasing the amount of money in circulation and also easing the burden of corporate loans.